The Variants that Effecting Creative Thinking Skills of Music Teachers - MALKOÇ, TÜLÜN (KAMLA-RAJ ENTERPRISES, 2015)
The objective of this research is to examine the viewpoints of music teacher candidates on activities about creativity in singing during pre-school music lessons and offering a number of suggestions for the music education program designers by making use of the results. The scale used in this research is applied to 124 students studying at various levels at Ataturk Faculty of Education (Department of music) Marmara University, during the 2014/15 academic year. In the light of the findings this research has concluded that the candidate teachers are aware of the necessary measures of creative activities in pre-school music education, and that they are capable of coming up with a solution to possible problems that can arise in music education. It is :detected that the students who took the general approaches in pre-school music education lessons, have developed more of an awareness of creativity than those who did not.
Keywords: Pre-school; Music Education; Music Tuition; Singing; Creativity